New modified Inverted Weibull Distribution: Properties and Applications to COVID-19 Dataset of Nepal - Chaudhary, Arun Kumar; Sapkota, Laxmi Prasad (Pravaha, 2021)
We have developed a four parameters new modified inverted Weibull distribution and we named it exponentiated exponential inverted Weibull distribution. Linear representation of probability density function, reliability function, hazard function, moments about the origin and its generating function, mean residual life function, order statistics, two entropies namely Renyi and q-Entropy, and mean deviation for the proposed distribution are presented. For the parameter estimation the maximum likelihood, least-square, and Cramer-Von-Mises estimation methods are used. The application of the proposed distribution is analyzed using the deaths case of the COVID-19 dataset of Nepal from 1st April to 14th May 2021.